More than “Alone with the Bible”: Reconceptualizing Religious Reading - Ronald, Emily K. (Sociology of religion, 2012)
The idea of a solitary reader of sacred texts distorts the importance of one form of religious reading and camouflages several equally important forms. Taking these other forms of reading into account not only gives us a better picture of how books are being used religiously, but also provides new avenues for studying the relationship between sacred texts and religious persons and reveals an arena where definitions of “religion” are being negotiated. Using data collected through the 2006–2007 work of the Spiritual Narratives in Everyday Life project, I will examine the role of reading as a spiritual practice, complicating this model in the process and suggesting new avenues for studying religious reading.